Antispermatogenic mechanism of trona is associated with lipid peroxidation but not testosterone suppression - Ayodeji F Ajayi; Roland E Akhigbe (Wolters Kluwer Medknow Publications, 2017)
Background: About half of the cases of infertility in couples have been attributed to male factor. Despite the claim in folklore medicine that trona (a sesquicarbonate or hydrated carbonate of sodium) causes fetal loss, its effect on male reproductive function has not been investigated. Aim: This study sought to provide scientific evidence on the effect of trona on sperm characteristics, male reproductive hormones and organs, and lipid peroxidation. Materials and Methods: Forty male Wistar rats of comparable weights were used for the study. Rats were randomized into four different groups. The control received 1 mL of distilled water orally, whereas those in groups 1, 2, and 3 (test groups) received orally, same volume of trona preparation corresponding to 100, 200, and 400 mg/kg body weight, respectively, for 28 days. Body weight was monitored throughout the study period, and at the end of the experiment, testicular morphometry, sperm characteristic, reproductive hormones, and malondialdehyde (MDA), an index of lipid peroxidation, were determined. Results: Sperm count, motility, progressibility, and percentage of normal sperm were significantly decreased in the trona-treated rats (P < 0.05). The percentage of abnormal sperm, luteinizing hormone, follicle stimulating hormone, and MDA were significantly increased in the treated rats (P < 0.05). Body weight, testicular morphometry, and testosterone level were comparable across all groups (P > 0.05). Conclusion: The study showed that trona has a dose-dependent deleterious effect on sperm characteristic. The antispermatogenic effect of trona was associated with lipid peroxidation but not testosterone.